IMPLIKASI KINERJA KARYAWAN LEMBAGA PENDIDIKAN XYZ BERDASARKAN JOB STRESSOR DAN KONFLIK KERJA - Nurul Giswi Karomah (JURNAL LENTERA BISNIS, 2015)
Analysis of the effect of Job Stressor and Work conflict on employee performance in PTS XYZ Jakarta. The study was conducted to determine how much influence the job stressors on Employee performance in PTS XYZ, and determine how much influence the job stressor  and conflict working together on employee performance in PTS XYZ, Jakarta.  This study used a survey method using questionnaires as a research instrument. The population in this study were 60 employee PTS XYZ in Jakarta and sampled in this study as many as 60 people. This research conducted in March to April 2014.Data analysis technique used is descriptive analysis technique based on the opinions of respondents of the research instrument in the form of questionnaire. Hypothesis testing is using a computer with the use of SPSS 17.0 windows program. The result showed there were significant negative effect of job stressor and work conflict on employee performance either partially or jointly (stimulatory). Key word : Job Stressor, Work Conflict, Performance